Assessment of Glossostigma elatinoides and Bacopa caroliniana to remediate landfill leachate through landscape ecology model system - Qurratu Aini binti Mat Ali (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2016)
The environmental pollution resulting from solid waste disposal at landfills is a severe problem. Many landfills in Malaysia have increased waste generation without proper disposal procedures. Heavy metals or inorganic contaminants exhibited in landfill sites in the form of dust, gas and leachate due to anthropogenic activities may result is serious environmental problems when they transport into the atmosphere, soil, surface water and groundwater without filtration or treatment system. Thus, this study assesses heavy metals sequestration rate of Glossostigma elatinoides and Bacopa caroliniana at different concentrations and different types of heavy metal in single element and hybrid elements at four different periods (week 1 until week 4) through an in vitro model system. This study also identifies heavy metals concentration in landfill soil. The concentration of several heavy metals contaminants (Al, Mn, Mg, Fe, Cu, Cr, Cd, Zn, Ni and Pb) in landfill soil and level of toxicity in the soil were evaluated from seven different localities. Factors influencing the concentration of heavy metal contaminants in landfill soil were the composition and compound of waste, degree of waste compaction, types of soil, evapotranspiration, landfill class and age, landfill area, climate and other environmental factors. The analysis of variance established significant to highly significant differences (P<0.001) between landfill soil and heavy metal concentration. From the findings, Cu, Zn, Cd and Pb concentration were found in landfill soil of Sungai Sabai landfill which exceeded the standard limit of natural soil. The four highest metals detected in all landfill sites were Al, Fe, Mn and Mg can cause soil contamination. The experimental in vitro model system established that the sequestration rate for single metals experiment by G.elatinoides and B.caroliniana individually showed (0.81 ± 0.006189 mg/L ) and (0.36 ± 0.004 mg/L) efficiency of Iron. Whereas the sequestration rates for hybrid metals experiment revealed that G.elatinoides presented (0.43 ± 0.0074 mg/L) and B.caroliniana (0.3220 ± 0.0063 mg/L) efficiency of Magnesium. Both single and hybrid experiments were conducted in different concentration ranges at different incubation periods. Interestingly, both G.elatinoides and B.caroliniana have the ability to sequester all four types of heavy metals at same trends which Fe>Mg>Mn>Al for single model system and Mg>Mn>Fe>Al for hybrid model system. The hybrid results showed that the interactive pattern was antagonistic when all metals were combined as Mg has reduced the sequestration rate of Al, Fe and Mn. The combination of Al, Fe and Mn without Mg showed that the interactive effects between Al, Fe and Mn were synergistic. The plants were able to sequester all heavy metals in a linear relationship with the incubation period, as the sequestration rates were increased with increased concentrations and periods for Al which decreased after long exposure. The result showed that certain metal removal efficiencies were increased initially by increasing of time and concentration. Thus, in this study both G.elatinoides and B.caroliniana are a good and potential bio-sequester agent to clean-up heavy metals contaminant in landfill soil and groundwater. In order to use these plants on a large scale, some factors need to be highlighted such as plant capabilities and tolerance towards level of heavy metal contaminants, plant species sequestration rate as well as type of contaminants. All factors may assist in achieving the effectiveness of plant sequestration rate.